2015
DOI: 10.3390/molecules200712481
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Aspirin Suppresses NF-κB Signaling in Estrogen Receptor Negative Breast Cancer Cells in Vitro and in Vivo

Abstract: Estrogen receptor negative (ER(−)) breast cancer is aggressive, responds poorly to current treatments and has a poor prognosis. The NF-κB signaling pathway is implicated in ER(−) tumorigenesis. Aspirin (ASA) is chemopreventive against ER(+) but not for ER(−) breast cancers. Nitric oxide-releasing aspirin (NO-ASA) is a safer ASA where ASA is linked to an NO-releasing moiety through a spacer. In vitro, we investigated anti-proliferation effects of NO-ASA (para-and meta-isomers) against ER(−) breast cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…However, the association between aspirin treatment and HER-2-positive breast cancer has not been studied in detail. Nath et al proved that aspirin inhibited HER-2-positive breast cancer SKBR-3 cell growth by regulating nuclear factor κB (NF-κB) activity [31]. Our study indicated that aspirin exerted an anticancer activity in the HER-2-positive breast cancer cell lines AU-565, BT-474 and SKBR-3 by inhibiting their proliferation and colony-forming abilities, regulating cell cycle progression, and inducing apoptosis, through the activation of AMPK signaling.…”
Section: Discussionsupporting
confidence: 52%
“…However, the association between aspirin treatment and HER-2-positive breast cancer has not been studied in detail. Nath et al proved that aspirin inhibited HER-2-positive breast cancer SKBR-3 cell growth by regulating nuclear factor κB (NF-κB) activity [31]. Our study indicated that aspirin exerted an anticancer activity in the HER-2-positive breast cancer cell lines AU-565, BT-474 and SKBR-3 by inhibiting their proliferation and colony-forming abilities, regulating cell cycle progression, and inducing apoptosis, through the activation of AMPK signaling.…”
Section: Discussionsupporting
confidence: 52%
“…It should be noted that although structure-activity studies with NO-aspirin had indicated that NO was pivotal for its anticancer effects [233] it also became apparent that in cases where the spacer was aromatic, the biological actions may have been due to formation of a putative quinone methide (QM) intermediate [234236]. NO-NSAIDs have shown efficacy in various animal models of cancer, including a rat model of colonic adenocarcinoma [237], Min (AP C Min/+ ) mouse [238], F344 rats treated with the carcinogen, azoxymethane [239], pancreatic cancer [240], urinary bladder cancer [241], and estrogen receptor negative breast cancer [242]. Molecular targets of NO-NSAIDs in cancer have been thoroughly reviewed elsewhere [25, 230].…”
Section: Modulation Of No Levels As a Strategy To Treat Cancermentioning
confidence: 99%
“…High iNOS expression is associated with favorable prognoses in ovarian [242] and lung cancers [284]. Overexpression of iNOS by gene transfer in prostate and colon cancer cells produced enhanced amounts of NO increasing the sensitivity of these cells to cisplatin-induced cell death [345] or to radiation therapy [346].…”
Section: Induction Of Inos And/or Cbs/cse As a Strategy To Treat Cmentioning
confidence: 99%
“…Nuclear factor‐κB (NF‐κB) plays an important role in the development of various malignancies, including breast cancer . Previous research has shown that NF‐κB can be constitutively active in ER‐negative breast cancer cell lines, and thus targeting NF‐κB could be an important target for the treatment of ER‐negative breast cancers . In a recent report, oleuropein was reported to modulate IL‐1β–stimulated NF‐κB activation in chondrocytes .…”
Section: Introductionmentioning
confidence: 99%